(untitled) (Journal of Business Management and Accounting, 2016)
Franchising is the fastest growing method of doing business these days, however, there is little academic research to guide or regulate industry practices. Thus, this research investigated the financial planning process in developing a new franchise system. This study used action research methodology to develop a new practical framework of financial planning for a new franchise system within the Malaysian government department franchise regulators. Three main action research cycles were conducted with three new franchise systems seeking to register with the Registrar of Franchise Malaysia (ROF). To triangulate the findings of the action research, the researcher also presented them at a National Franchise Workshop (NFW). These activities showed that the process of financial planning for a new franchise system should comprise 14elements with specific linkages. These practical frameworks for financial planning in a new franchise system were adopted by the ROF to be used as guideline in the process of developing a new franchise system and serve as evaluation tools for franchise registration.